Designing Tutoring for Equitable Instruction in Urban Schools - Tim Morse; Giang-Nguyen Thi Nguyen (Journal of Asian Primary Education (JoAPE), 2025)
This manuscript reports a single-case design study that was conducted in an after-school program. Three kindergarten students attending an urban elementary school in the southeastern United States acquired foundational mathematics and reading skills after receiving instruction based on a conceptual explicit instruction approach for presenting short-duration lessons. Further, the students demonstrated skill maintenance and generalization two weeks following skill acquisition. As a result of the study’s positive results, the intervention is now serving as the basis for the school’s development of a schoolwide tutoring program for all students. Tutoring is explained within the context of a school’s multi-tiered system of supports that is designed to track each student’s school performance and match the school’s system of interventions to each student’s individualized needs. Additionally, the merits of tutoring and ways to differentiate it so that it is scalable and sustainable in urban schools, particularly those that are in high-poverty areas and are under-resourced, are discussed. Suggestions for additional research are presented.